Power of being different: a successful formula - "Carinci, John Paul" (Mumbai, 2007)
The beauty of this book is that it covers a wide range of topics to improve your life. Topics Covered include : 1 The power behind belief. 2 How the mind controls the body. 3 How to get enthusiasm back in your life. 4 Understanding and forming good habits. 5 Understanding negativity and how to avoid it. 6 How to use your mind as a filter. 7 How to use "positive self-suggestion". 8 How to maximize your subconscious mind. 9 How to use "positive visualization". The Power Of Being Different can help you transform your life, and achieve all you truly desire. Stand up! Stand out! Be Different Today!
Keywords: "Success, Conduct of life, Difference, Psychology, Self r"